Impact on local air quality of the Danish landworks in the fixed link across Øresund. - Berkowicz, Ruwim; Fenger, Jes; Gudmundsson, Henrik; Vignati, Elisabetta; Wagner, Morten (Proceedings from the Annual Transport Conference at Aalborg University, 1996)
The combined bridge and tunnel link between Sweden and Denmark (the Øresund Link) and the related land constructions are expected to be in operation around the turn of the century. This new link across the Øresund and the island Amager may result in significant changes in traffic pattern and traffic intensity - and therefore changes in air quality in some areas can not be excluded. An investigation initiated in 1994 on the Danish side of the link comprises monitoring of present air pollution at the Airport Motorway and model evaluations of future pollution levels at the motorway and in six street canyons. For all locations the pollution levels are calculated for the present situation and for scenarios for the years 2000 and 2010 both with and without the fixed link. For the future scenarios an expected development of vehicle technology is taken into account. It appears that the general air quality in the area will not be worsen. Only for benzene there is a continued risk of violation of limit values; this may however be changed by planned emission restrictions. A special situation however, may arise near the apartment buildings "Vinkelhusene". Here it has been decided to cover about 700 m of the motorway, in order to reduce noise and to avoid a barrier effect. This will result in increased pollution levels near the tunnel exits. All calculations are performed with dispersion models developed at the National Environmental Research Institute and are based on traffic scenarios from a traffic model developed by Anders Nyvig Ltd.